Liquid crystal cell with a tapered optical fiber as an active element to optical applications - Moś, Joanna Ewa; Stasiewicz, Karol Antoni; Jaroszewicz, Leszek Roman (Photonics Letters of Poland, 2019)
The work describes the technology of a liquid crystal cell with a tapered optical fiber as an element providing light. The tapered optical fiber with the total optical loss of 0.22 ± 0.07 dB, the taper waist diameter of 15.5 ± 0.5 μm, and the elongation of 20.4 ± 0.3 mm has been used. The experimental results are presented for a liquid crystal cell filled with a mixture 1550* for parallel orientation of LC molecules to the cross section of the taper waist. Measurement results show the influence of the electrical field with voltage in the range of 0-200 V, without, as well as with different modulation for spectral characteristics. The sinusoidal and square signal shapes are used with a 1-10 Hz frequency range. Full Text: PDF References Z. Liu, H. Y. Tam, L. Htein, M. L.Vincent Tse, C. Lu, "Microstructured Optical Fiber Sensors", J. Lightwave Technol. 35, 16 (2017). CrossRef T. R. Wolinski, K. Szaniawska, S. Ertman1, P. Lesiak, A. W. Domański, R. Dabrowski, E. Nowinowski-Kruszelnicki, J. Wojcik "Influence of temperature and electrical fields on propagation properties of photonic liquid-crystal fibres", Meas. Sci. Technol. 17, 5 (2006). CrossRef K. Nielsen, D. Noordegraaf, T. Sørensen, A. Bjarklev,T. Hansen, "Selective filling of photonic crystal fibres", J. Opt. A: Pure Appl. Opt. 7, 8 (2005). CrossRef A. A. Rifat, G. A. Mahdiraji, D. M. Chow, Y, Gang Shee, R. Ahmed, F. Rafiq, M Adikan, "Photonic Crystal Fiber-Based Surface Plasmon Resonance Sensor with Selective Analyte Channels and Graphene-Silver Deposited Core", Sensors 15, 5 (2015) CrossRef Y. Huang, Z.Tian, L.P. Sun, D. Sun, J.Li, Y.Ran, B.-O. Guan "High-sensitivity DNA biosensor based on optical fiber taper interferometer coated with conjugated polymer tentacle", Opt. Express 23, 21 (2015). CrossRef X. Wang, O. S. Wolfbeis, "The 2016 Annual Review Issue", Anal. Chem., 88, 1 (2016). CrossRef Ye Tian, W. Wang, N. Wu, X. Zou, X.Wang, "Tapered Optical Fiber Sensor for Label-Free Detection of Biomolecules", Sensors 11, 4 (2011). CrossRef O. Katsunari, Fundamentals of Optical Waveguides, (London, Academic Press, (2006). DirectLink A. K. Sharma, J. Rajan, B.D. Gupta, "Fiber-Optic Sensors Based on Surface Plasmon Resonance: A Comprehensive Review", IEEE Sensors Journal 7, 8 (2007). CrossRef C. Caucheteur, T. Guo, J. Albert, "Review of plasmonic fiber optic biochemical sensors: improving the limit of detection", Anal. Bioanal.Chem. 407, 14 (2015). CrossRef S. F. Silva L. Coelho, O. Frazão, J. L. Santos, F. X.r Malcata, "A Review of Palladium-Based Fiber-Optic Sensors for Molecular Hydrogen Detection", IEEE SENSORS JOURNAL 12, 1 (2012). CrossRef H. Waechter, J. Litman, A. H. Cheung, J. A. Barnes, H.P. Loock, "Chemical Sensing Using Fiber Cavity Ring-Down Spectroscopy", Sensors 10, 3 (2010). CrossRef S. Zhu, F. Pang, S. Huang, F.Zou, Y.Dong, T.Wang, "High sensitivity refractive index sensor based on adiabatic tapered optical fiber deposited with nanofilm by ALD", Opt. Express 23, 11 (2015). CrossRef L. Zhang, J. Lou, L. Tong, "Micro/nanofiber optical sensors", Photonics sensor 1, 1 (2011). CrossRef L.Tong, J. Lou, E. Mazur, "Single-mode guiding properties of subwavelength-diameter silica and silicon wire waveguides", Opt. Express 11, 6 (2004). CrossRef H. Moyyed, I. T. Leite, L. Coelho, J. L. Santos, D. Viegas, "Analysis of phase interrogated SPR fiber optic sensors with bimetallic layers", IEEE Sensors Journal 14, 10 (2014). CrossRef A. González-Cano, M. Cruz Navarette, Ó. Esteban, N. Diaz Herrera , "Plasmonic sensors based on doubly-deposited tapered optical fibers", Sensors 14, 3 (2014). CrossRef K. A. Stasiewicz, J.E. Moś, "Threshold temperature optical fibre sensors", Opt. Fiber Technol. 32, (2016). CrossRef L. Zhang, F. Gu, J. Lou, X. Yin, L. Tong, "Fast detection of humidity with a subwavelength-diameter fiber taper coated with gelatin film", Opt. Express 16, 17 (2008). CrossRef S.Zhu, F.Pang, S. Huang, F. Zou, Q. Guo, J. Wen, T. Wang, "High Sensitivity Refractometer Based on TiO2-Coated Adiabatic Tapered Optical Fiber via ALD Technology", Sensors 16, 8 (2016). CrossRef G.Brambilla, "Optical fibre nanowires and microwires: a review", J. Optics 12, 4 (2010) CrossRef M. Ahmad, L.L. Hench, "Effect of taper geometries and launch angle on evanescent wave penetration depth in optical fibers", Biosens. Bioelectron. 20, 7 (2005). CrossRef L.M. Blinov, Electrooptic Effects in Liquid Crystal Materials (New York, Springftianer, 1994). CrossRef L. Scolari, T.T. Alkeskjold, A. Bjarklev, "Tunable Gaussian filter based on tapered liquid crystal photonic bandgap fibre", Electron. Lett. 42, 22 (2006). CrossRef J. Moś, M. Florek, K. Garbat, K.A. Stasiewicz, N. Bennis, L.R. Jaroszewicz, "In-Line Tunable Nematic Liquid Crystal Fiber Optic Device", J. of Lightwave Technol. 36, 4 (2017). CrossRef J. Moś, K A Stasiewicz, K Garbat, P Morawiak, W Piecek, L R Jaroszewicz, "Tapered fiber liquid crystal hybrid broad band device", Phys. Scripta. 93, 12 (2018). CrossRef Ch. Veilleux, J. Lapierre, J. Bures, "Liquid-crystal-clad tapered fibers", Opt. Lett. 11, 11 (1986). CrossRef R. Dąbrowski, K. Garbat, S. Urban, T.R. Woliński, J. Dziaduszek, T. Ogrodnik, A,Siarkowska, "Low-birefringence liquid crystal mixtures for photonic liquid crystal fibres application", Liq. Cryst. 44, (2017). CrossRef S. Lacroix, R. J. Black, Ch. Veilleux, J. Lapierre, "Tapered single-mode fibers: external refractive-index dependence", Appl. Opt., 25, 15 (1986). CrossRef J.F. Henninot, D. Louvergneaux , N.Tabiryan, M. Warenghem, "Controlled Leakage of a Tapered Optical Fiber with Liquid Crystal Cladding", Mol. Cryst.and Liq.Cryst., 282, 1(1996). CrossRef